Wpływ domieszki sosny w drzewostanie bukowym na intensywność wypłukiwania węgla, żelaza i glinu z poziomu organicznego i próchnicznego gleb bielicowo-rdzawych - Jonczak, Jerzy (Leśne Prace Badawcze, 2012)
During the years 2008-2009, at the £ysomice Forest Subdistrict (Forest District Leœny Dwór, Regional Directorate of State Forest Szczecinek) comparative studies of lysimeter water chemistry were conducted in a 120-year-old beech stand and beech stand of similar age with an admixture of pine and spruce. Three zero-tension lysimeters were installed beneath the organic and humic horizons of Dystric Arenosols under the beech and pine canopies. Lysimetric water was collected after every rainfall, measured volumetrically, filtered and analyzed on pH and concentration of dissolved organic carbon (DOC), iron and aluminium. The chemical composition of leachates differed between beech and mixed stands. The pH of water from the organic horizon, on average for the entire study period, was 4.89 in the beech stand and 3.71 in the mixed stand. Lysimeter water from the humic horizon had an average pH of 4.43 and 3.73 for the beech and mixed stands respectively. The concentration of DOC and Fe and Al in the lysimeter water was higher in the mixed stand than in the pure beech. The quantity of DOC and Al leached during one year per unit of soil mass was similar in the both stands, and the amount of Fe was significantly higher in stands with pine admixture than in pure beech stands.